- #1

jrand26

- 11

- 0

For example, our lecturer did on the board, <Sx+|Sz|Sx+>

So what I would do is, ignoring any factors of 1/sqrt(2) or 1/2 or hbar.

Sx+ = |+> + |->

Sz = |+><+|-|-><-|

=> ( |+> + |-> )(|+><+|-|-><-|)( |+> + |->)

This is where I get stuck, the lecturer goes straight from this to,

(<+| + <-|)(|+> - |->)

When I try to expand it out, for the first two terms, I get stuck at

|+> * |+><+|-|-><-| = |+>|+> <+|-|-> <-|+> ??

I can see that the |+> can go with the <-| at the end, but does it go onto the expectation as well? How does that work?

Does |+> <+|-|-> = <+|+>|-|-> ?

That doesn't look right to me. Any help is appreciated.